Endovascular Embolization of Large Hepatic Arteriovenous Fistulas - Johnson, Stephen P. (Thieme Medical Publishers, 2007)
Treatment of hepatic artery to portal vein fistulas (HAPFs) has shifted in the past two decades from surgical resection of the involved liver to embolization. A uniform technique for percutaneous intervention has not been established because the approach is influenced by the size, location, and number of feeding arteries. We report two cases of HAPFs treated with embolization at our institution. Different outcomes in these two patients illustrate several fundamental principles in the treatment of HAPFs.